Emotions, identity, and profanity: Swearing as expression in the Heartbeat novel - Nasir, Chairina; Anisah, Anisah; Qismullah Yusuf, Yunisrina; Zahari, Maula Azkia (UNIB Press, 2025)
Swearing is a linguistic phenomenon that serves multiple functions in communication, including the expression of emotions, reinforcement of social bonds, and intensification of speech. The novel Heartbeat by Jealoucy features characters who frequently engage in swearing across various contexts. However, there is limited research examining the types and motivations of swearing in contemporary literary works, particularly in modern novels. This study aims to identify the types of swearing (Ljung, 2011) employed by the characters and to analyze the motivations behind their usage (Andersson & Trudgill, 1992). Using a qualitative descriptive approach, the research involves close reading and note-taking to examine instances of swearing within the text. The data were categorized into types of swearing and the motivations behind swearing. The analysis focuses on the context, function, and underlying reasons for each instance. The findings reveal that the characters use swearing 44 times throughout the novel, with expletive interjections identified as the most frequently used type. Psychological motivations, such as expressing anger, frustration, or surprise, emerge as the most dominant reasons for swearing. These findings suggest that swearing contributes significantly to character development and the authenticity of dialogue in fictional narratives. Future research may investigate how swearing differs across literary genres or how it affects readers’ perceptions.